2019
DOI: 10.1002/macp.201800574
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Helical Rod–Coil Block Polymers by the Combination of ATRP and Pd(II)‐Initiated Isocyanides Polymerizations

Abstract: A bifunctional initiator containing propargyl bromoisobutyrate and alkyne‐Pd(II) (PBB‐Pd(II)) is designed and synthesized. The propargyl bromoisobutyrate unit of PBB‐Pd(II) can initiate the atom transfer radical polymerization (ATRP) of vinyl monomers, while the Pd(II) complex can initiate the polymerization of phenyl isocyanides. Both the ATRP and Pd(II)‐mediated isocyanide polymerization are proceeded in living/controlled manner. Thus, combining the two living polymerizations, a series of well‐defined block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In addition, the linear diblock copolymer poly­( 1L 70 - b - 2b 280 ) ( M n = 196 kDa, PDI = 1.19), which possessed similar components to (poly- 1L 10 ) 7 -CD-(poly- 2b 20 ) 14 , was synthesized according to previous literature (Figure S22). The CPL measurement showed that poly­( 1L 70 - b - 2b 280 ) was CPL-active, but its g lum value was only 2.6 × 10 –3 (Figure S23), which was much lower than that of (poly- 1L 10 ) 7 -CD-(poly- 2b 20 ) 14 , indicating that the Janus structure advantaged the CPL performance of copolymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the linear diblock copolymer poly­( 1L 70 - b - 2b 280 ) ( M n = 196 kDa, PDI = 1.19), which possessed similar components to (poly- 1L 10 ) 7 -CD-(poly- 2b 20 ) 14 , was synthesized according to previous literature (Figure S22). The CPL measurement showed that poly­( 1L 70 - b - 2b 280 ) was CPL-active, but its g lum value was only 2.6 × 10 –3 (Figure S23), which was much lower than that of (poly- 1L 10 ) 7 -CD-(poly- 2b 20 ) 14 , indicating that the Janus structure advantaged the CPL performance of copolymers.…”
mentioning
confidence: 99%
“…The CAC values for (poly- 1L 20 ) 7 -CD-(poly- 2c 10 ) 14 , (poly- 1L 20 ) 7 -CD-(poly- 2c 20 ) 14 , and (poly- 1L 20 ) 7 -CD-(poly- 2c 40 ) 14 were 21.2, 34.1, and 48.4 mg/L, respectively (Figure S28). Meanwhile, the linear diblock copolymer poly­( 1L 140 - b - 2c 140 ) ( M n = 101 kDa, PDI = 1.22) that had similar components to (poly- 1L 20 ) 7 -CD-(poly- 2c 10 ) 14 was prepared (Figure S29), and its CAC was 36.4 mg/mL (Figure S30), obviously larger than that of (poly- 1L 20 ) 7 -CD-(poly- 2c 10 ) 14 . The transmission electron microscope (TEM) and dynamic light scattering (DLS) results for (poly- 1L 20 ) 7 -CD-(poly- 2c 10 ) 14 , (poly- 1L 20 ) 7 -CD-(poly- 2c 20 ) 14 , and (poly- 1L 20 ) 7 -CD-(poly- 2c 40 ) 14 in aqueous solutions are depicted in Figure .…”
mentioning
confidence: 99%